A BRIEF SCENARIO OF THE ESTUARINE MESOZOOPLANKTON IN NORTHEASTERN BRAZIL: A TOOL FOR CONSERVATION - Garcia, Tatiane Martins; Cascon, Helena Matthews; Tundisi, Takako Matsumura; Leitão, Sigrid Neumann (Arquivos de Ciências do Mar, 2014)
The Brazilian coast stretches itself along the western Atlantic Ocean, covering 7,367 km, being sorted out into five sectors, three of which are located in the northeastern region. In these sectors, estuaries can be classified as permanent or temporary, the latter holding estuarine characteristics only during part of the year. Studies carried out on estuarine mesozooplankton in that region have been conducted since the 1960s. In the rainy season, the marine species penetrate into the estuary during the high tide, whereas during the low tide limnetic species inhabit this ecosystem. In the dry season, there is a smaller freshwater contribution to the estuary with a more pronounced marine influence; under these conditions the zooplanktonic community is composed by euryhaline marine organisms. This approach should be encouraged, as well as studies throughout the whole of the Northeast region, since there are still many estuaries where this taxonomic group has never been investigated